Generative Artificial Intelligence in Game Design: A Narrative Review - Al-Surayhi , Mazen Mohammed; Al-Qahtani , Mohammed Rashid; Al-Marshadi , Saleh Nasser; Al-Ghamdi , Ahmad Abdullah Qeran; Al-Surayhi , Monther Mohammed (Journal of Ecohumanism, 2025)
Generative artificial intelligence (AI) is redefining the landscape of game design by enabling the automated creation of high-quality content such as 2D/3D assets, environments, and personalized narratives. This paper presents a narrative review of recent advancements (2018–2024) in generative AI applications within the gaming industry, focusing on tools like GANs, VAEs, LLMs, and diffusion models. The study highlights how these technologies enhance development efficiency, foster creativity, and empower indie developers by reducing production costs and democratizing access. Moreover, the integration of generative AI with immersive technologies such as VR and AR is creating more responsive and emotionally engaging gameplay experiences.Despite these advantages, several challenges persist. These include ensuring playability, maintaining narrative originality, addressing ethical concerns such as bias and intellectual property, and avoiding content homogenization. The study proposes practical recommendations for developers and researchers to adopt hybrid workflows, promote AI literacy, establish ethical standards, and enhance inclusive access to AI tools. By striking a balance between innovation and human creativity, the paper argues that generative AI can elevate video games into powerful platforms for cultural expression and social engagement.